The Implementation of Urban Drainage Maintenance to Reduce Inundation Risk: Case Study in Tegal, Indonesia - Dewanti; Wulan Nurindah Sari; Ichiki Atsushi; Shimizu Toshiyuki (The Journal of Indonesia Sustainable Development Planning, 2020)
Coastal cities with low elevation and mild slopes tend to be more vulnerable to the threat of floods and inundations. Expansion of impermeable areas caused by land conversion greatly diminishes a city’s ability to cope with the threat. Urban drainage systems play a crucial role in controlling excess surface water and reducing the threat of flood and inundation. To maintain an urban drainage system within an optimumcondition and to reduce inundation risk, various types of drainage maintenance activities have been implemented in Tegal. This research was conducted in five inundationproneareas in Tegal to analyze the impact of those maintenance activities to urban drainage conditions andin reducing inundation. GIS and statistical analysis revealed that fromthe numerousurban drainage maintenance activities that have been performed, drainage sediment cleanuphas the most obvious impact on drainage conditions and in reducing inundation.